2013
DOI: 10.1118/1.4812425
|View full text |Cite
|
Sign up to set email alerts
|

Organ S values and effective doses for family members exposed to adult patients following I-131 treatment: A Monte Carlo simulation study

Abstract: The authors performed realistic assessments of 131I organ S values and effective dose per time-integrated activity from adult patients treated for hyperthyroidism and DTC to family members. In addition, the authors' studies consider Monte Carlo simulated "mother and baby∕child" exposure scenarios for the first time. Based on these results, the authors reconfirm the strong conservatism underlying the point source method recommended by the US NRC. The authors recommend that various factors such as the type of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
(15 reference statements)
1
10
0
Order By: Relevance
“…Recently, several investigators have developed NURBS/polygonal mesh (PM)-based hybrid phantom that can address the limitations of the voxel phantom and be deformed in various postures. 12,[15][16][17][18] Based on this, the deformed hybrid phantom has been modeled with various ages and shapes. In addition, a program to convert the hybrid phantom to DICOM was developed for the purpose of clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several investigators have developed NURBS/polygonal mesh (PM)-based hybrid phantom that can address the limitations of the voxel phantom and be deformed in various postures. 12,[15][16][17][18] Based on this, the deformed hybrid phantom has been modeled with various ages and shapes. In addition, a program to convert the hybrid phantom to DICOM was developed for the purpose of clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the line source model is a good approximation for 99m Tc, 18 F, and 131 I used for remnant ablations. In Han et al (2013), more realistic adult and child phantoms were used to compute dose rates with static activity distribution for hyperthyroid patients and patients with differentiated thyroid cancer. This study confirmed that the point source approximation is too conservative but also that the activity distribution inside the patient strongly affected the calculation results.…”
Section: Discussionmentioning
confidence: 99%
“…Organ dose rates were estimated in the exposed individual using the kerma approximation. This approximation is known to be accurate to~2% for 131 I due to the primary photon energy of 364 keV (Han et al 2013). The kerma approximation was implemented using the volume-averaged track length fluence estimator along with the kerma factors (heating numbers) from the MCNP6 nuclear data tables.…”
Section: Computational Phantom Modelsmentioning
confidence: 97%
“…Han et al employed Monte Carlo simulation for stylized phantoms developed previously by ORNL for 131 I source distributions in the thyroid, abdomen and whole body (Han et al 2013). These phantoms were placed at various separation distances and two exposure scenarios (face-to-face, standing; and side-by-side, lying).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation